Early clinical factors predicting the development of critical disease in Japanese patients with COVID‐19: A single‐center, retrospective, observational study. Issue 4 (1st November 2020) - Higuchi, Takatoshi; Nishida, Tsutomu; Iwahashi, Hiromi; Morimura, Osamu; Otani, Yasushi; Okauchi, Yukiyoshi; Yokoe, Masaru; Suzuki, Norihiro; Inada, Masami; Abe, Kinya
Abstract: The factors predicting the progression of coronavirus disease‐2019 (COVID‐19) from mild to moderate to critical are unclear. We retrospectively evaluated risk factors for disease progression in Japanese patients with COVID‐19. Seventy‐four patients with laboratory‐confirmed COVID‐19 were hospitalized in our hospital between February 20, 2020, and June 10, 2020. We excluded asymptomatic, non‐Japanese, and pediatric patients. We divided patients into the stable group and the progression group (PG; requiring mechanical ventilation). We compared the clinical factors. We established the cutoff values (COVs) for significantly different factors via receiver operating characteristic curve analysis and identified risk factors by univariate regression. We enrolled 57 patients with COVID‐19 (median age 52 years, 56.1% male). The median time from symptom onset to admission was 8 days. Seven patients developed critical disease (PG: 12.2%), two (3.5%) of whom died; 50 had stable disease. Univariate logistic analysis identified an elevated lactate dehydrogenase (LDH) level (COV: 309 U/l), a decreased estimated glomerular filtration rate (eGFR; COV: 68 ml/min), lymphocytopenia (COV: 980/μl), and statin use as significantly associated with disease progression. However, in the Cox proportional hazards analysis, lymphocytopenia at admission was not significant. We identified three candidate risk factors for progression to critical COVID‐19 in adult Japanese patients: statin use, elevated LDH level, and decreased eGFR. Highlights: To evaluate risk factors for disease progression in Japanese patients with COVID‐19, we examined seventy‐four patients with laboratory‐confirmed COVID‐19. Seven patients (12.2%) developed critical disease requiring mechanical ventilation, two (3.5%) of whom died. We identified three candidate risk factors for progression to critical COVID‐19 in adult Japanese patients: statin use elevated LDH level and decreased eGFR.